Analisis Kepuasan Konsumen Terhadap Kualitas Pelayanan dan Harga Produk pada Supermarket dengan Menggunakan Metode Importance Performance Analysis (IPA) - Melfa Yola; Duwi Budianto (Jurnal Optimasi Sistem Industri, 2013)
Currently, the number of retail companies grow rapidly. This condition make high level competition between retailing in Indonesia and each of company need to have effective strategy to survive in retail business. Beside, a number of big company also take opportunity to expand retail business, not only into big size category (e.q. Hypermarket) but also into small size such as mini market. It can be big challenges for Small Medium Enterprise to handle this situation. The Objective of this paper is to explain the priority of importance factors of customer satisfaction in a supermarket, as a strategy for company to survive in retail business. Data is collected by spreading questioner to 385 respondents, and processed by using Importance-Performance Analysis (IPA) to compare between customer's expectations and company's perfomances. There are 11 factors that company must pay attention and it is shown in Cartesian DiagramKeywords: Supermarket, customer satisfaction analysis, Importance Performance Analysis